Peak performance : aligning the hearts and minds of your employees - Katzenbach, Jon R., 1932- (Boston, MA : Harvard Business School Press, 2000)
Explains how companies benefit from peak performance in their front-line employees and shares how businesses can improve the performance of their own employees, and in turn improve their company's success.
Includes bibliographical references and index.
Adult
Keywords: Employee motivation; Personnel management; Employee motivation; Personnel management